HYDROLOGICAL DISCHARGE DETERMINATION AND SEDIMENTATION ANALYSIS AT CIPUNAGARA ESTUARY, IN SUBANG - Irham Dinan - NIM 155 13 018, Muhammad
Coastal area is very dynamic. The sedimentation in estuary causes coastal morphological changes. Sediment which is carried by river flow will be acumulated in the estuary. Sedimentation phenomenon also occurs in Cipunagara Estuary, Subang, Indonesia and then causing the accretion. Due to this occurence of accretion, a study is to determine the hidrologycal discharge, calculate the total sediment transport rate, and analyze the area of sedimentation in the Cipunagara estuary. In this thesis, the determination of hidrological discharge reffered to SNI 2145-2016 while the analysis of sedimentation reffered to Van Rijn's analytical equations. The frequency analysis of maximum daily rainfall in Cipunagara watershed was done to obtain the value of rainfall plan. The rainfall plan was then used to calculate flood discharge plan with using HSS Nakayasu method. The flood discharge plan with 2-years return period was chosen to determine the flowrate at STA 1 in Cipunagara River. Furthermore, the flowrate and sediment characteristics at STA 1 is used as the parameter to determine the total sediment transport rate at STA 1. The total sediment transport rate from January to December are calculated to obtain the volumetric value of the transported sediment which then used for the area of sedimentation analysis at STA6 and STA 9 in Cipunagara estuary. In this study, the value of flood discharge plan from January to December was obtained as, 328,41 m3/s, 275,96 m3/s, 247,62 m3/s, 300,25 m3/s, 212,19 m3/s, 129,84 m3/s , 142,14 m3/s, 67,83 m3/s, 52,93 m3/s, 160,33 m3/s, 266,60 m3/s, and 299,44 m3/s. The value of total sediment transport from January to December at STA 1 was obtained as 3.404,27 kg/s, 1.699,55 kg/s, 1.089,81 kg/s, 2388,09 kg/s, 567,34 kg/s, 55,08 kg/s, 88,34 kg/s, 0,20 kg/s, 0 kg/s, 159,30 kg/s, 1.476,38 kg/s, dan 2.359,60 kg/s . The area of sedimentation over one year at STA 6 with scheme A was 328,409 m2 and scheme B was 346,149 m2 ,while at STA 9 with scheme A was 187,662 m2, and scheme B was 208,679 m2.